Tesco Joins Campaign Against Cancer - New Straits Times, Noel Acherlam (2008)
Make a difference on July 27 by joining the Tesco Malaysia Walk For Life 2008 at Taman Tasik Titiwangsa to help raise funds for research into the prevention treatment and cure of cancer.